Musculoskeletal Pain and Brain Morphology: Oxytocin’s Potential as a Treatment for Chronic Pain in Aging - Lussier, Désirée; Cruz-Almeida, Yenisel; Ebner, Natalie C. (Frontiers in Aging Neuroscience, 2019)
Chronic pain disproportionately affects older adults, severely impacting quality of life and independent living, with musculoskeletal pain most prevalent. Chronic musculoskeletal pain is associated with specific structural alterations in the brain and interindividual variability in brain structure is likely an important contributor to susceptibility for the development of chronic pain. However, understanding of age-related structural changes in the brain and their associations with chronic musculoskeletal pain is currently limited. Oxytocin (OT), a neuropeptide present in the periphery and central nervous system, has been implicated in pain attenuation. Variation of the endogenous OT system (e.g., OT receptor genotype, blood, saliva, and cerebrospinal fluid OT levels) is associated with morphology in brain regions involved in pain processing and modulation. Intranasal OT administration has been shown to attenuate pain. Yet, studies investigating the efficacy of OT for management of chronic musculoskeletal pain are lacking, including among older individuals who are particularly susceptible to the development of chronic musculoskeletal pain. The goal of this focused narrative review was to synthesize previously parallel lines of work on the relationships between chronic pain, brain morphology, and OT in the context of aging. Based on the existing evidence, we propose that research on the use of intranasal OT administration as an intervention for chronic pain in older adults is needed and constitutes a promising future direction for this field. The paper concludes with suggestions for future directions in this emerging research field, guided by our proposed Model of Oxytocin’s Analgesic and Brain Structural Effects in Aging.